COMPARATIVE STUDY OF THE POETIC STYLES AND TECHNIQUES USED BY BYRON AND LERMONTOV - Ruzibayeva Aziza Kahramanovna (Web of Journals Publishing, 2024)
This comparative study examines the poetic styles and techniques used by two renowned Romantic poets, Lord Byron and Mikhail Lermontov. By analyzing their works, this article aims to highlight the similarities and differences in their approaches to poetry and the impact of their respective cultural backgrounds on their writing. Through a close examination of selected poems, such as Byron's "Childe Harold's Pilgrimage" and Lermontov's "Borodino," this study seeks to shed light on how these poets utilized various poetic devices to convey their thoughts, emotions, and reflections on life, love, nature, and society.
Keywords: Lord Byron, Mikhail Lermontov, Romantic poetry, poetic styles, techniques.